Hyper-IgE syndrome: a case report - Sanal, Özden; Göçmen, Ayhan; Tezcan, İlhan and Ersoy, Fügen and Adalıoğlu, Gönül (The Turkish Journal of Pediatrics, 1990)
A four-year-old-girl with hyper-IgE syndrome is presented. She had a coarse facial appearance, pruritic dermatitis, recurrent skin abscesses, pulmonary infection, spontaneous bone fractures, and an elevated serum IgE concentration. She has been treated with cimetidine, ascorbic acid and trimethoprim-sulfamethoxazole for the last two years and there has been no evidence of a severe infection.